Kontribusi Utang Luar Negeri, Sukuk dan Zakat Terhadap Pertumbuhan Ekonomi di Indonesia - Aisyah Nurhayati; Fitria Nur Farida; Hikmah Endraswati (ITB AAS INDONESIA Surakarta, 2026)
This study aims to examine the contribution of external debt, sovereign sukuk, and zakat to economic growth in Indonesia. The research employs a quantitative approach using time series data covering the period 2010–2024. Multiple linear regression is applied as the main analytical method. The empirical results indicate that external debt, sukuk, and zakat jointly have a significant effect on Indonesia’s economic growth. Partially, external debt exerts a positive and statistically significant impact, suggesting that external financing continues to play a productive role when managed efficiently and within sustainable limits. Zakat also shows a positive and significant effect, highlighting its strategic function as an Islamic social finance instrument in promoting inclusive economic growth through income redistribution and enhanced purchasing power among low-income households. In contrast, sovereign sukuk exhibits a positive but statistically insignificant effect, implying that its contribution to economic growth is more structural and long-term rather than immediate.